Efficacy of Rituximab for Refractory Pyoderma Gangrenosum-Like Ulcers in Granulomatosis With Polyangiitis Associated to Antiphospholipid Antibodies - Julia RIERA,; Jorge MUSURUANA,; Cecilia COSTA,; Javier CAVALLASCA, (Archives of Rheumatology, 2020)
Pyoderma gangrenosum (PG) is a neutrophilic dermatosis that most often presents with painful ulcerations of violaceous borders in lower limbs and/or trunk. PG treatment varies according to the severity of the lesion and may either respond to local therapies or require immunosuppressive agents. In this article, we present the case of an antiphospholipid antibody-positive 59-year-old female patient diagnosed with granulomatosis with polyangiitis who developed severe PG-like skin involvement that was responsive to rituximab therapy.